Transformation of University College to University: Academics’ Perception of the Challenges - Sara Asmawati, Shariffuddin; Jamal Rizal, Razali (University College TATI, 2020)
Transformation of university college to university is part of Malaysian government’s efforts to revolutionize higher education and to prepare its human capital to becoming a developed nation. Pressure of the transformation impacts the stakeholders in particular the academics who are responsible for carrying out most of the strategies to achieve the transformation objective. The study presents and analyses the challenges experienced by academics in the transformation process via qualitative research design. In the study, data were examined from academics’ responses to semi-structured interview questions and document analysis during which the transformation was progressively taking place at a Malaysian university college. The results show ten types of challenges were identified. The results provide evidence to various types of challenges experienced by the academics and its effects on them in the process of transforming university college to university. Thus, the results assist the policymakers, leaders of higher education providers and/or the management to make critical modification and improvement to relevant policies, resources, and capability in course-correcting their strategies towards attaining the objectives of transformation process.